Towards sustainable use of Marula (Sclerocarya birrea) in the Savannah woodlands of Zvishavane District, Zimbabwe - Ngorima, Gabriel T (My University, 2007)
The aim was to determine the availability of marula (Sclerocarya birrea) (A.Rich.) Hochst. Subsp.cafra (Sond.) Kokwaro trees for the harvesting of nut oils, through determining abundance, population structure and regeneration capacity, within the context of the socioeconomic and biophysical dimensions of villages in Zvishavane, Zimbabwe. Both arable and non arable lands in the study area were sampled within four randomly selected villages to measure species abundance, regeneration and population dynamics of the trees. The socioeconomic factors influencing marula commercialisation were determined through participatory rural appraisal (PRA) and household questionnaire survey techniques. Vegetation characteristics were assessed through the point centre quarter (PCQ) method by placement of transects across sampled villages. All households (100%) collected marula fruit for their household use, mainly for brewing marula beer, making jam and selling kernels for snacks or oil pressing. In 2005, the mass of marula harvest per household averaged 160 ± 18 (SD) kg, with a range of 50-800 kg within the study area. A linear regression analysis indicates no increase in mass of marula harvest with larger sizes of household (r2 = 0.0089, d.f = 50, p = 0.4048). In addition, household interviews revealed that there was no association between level of household wealth status and the household’s use of traditional medicine from marula trees (χ2 = 0.2233, d.f = 2, p = 0.8944). The vegetation survey indicated a elatively high density of marula within the study area of 8.03 ± 3.19 stems ha-1. There was a significant difference in marula densities between arable and non arable land uses (F1, 197 = 11.92, p=0.001). The arable land had 6.40 ± 5.29 stems ha-1 while non arable land had three times more at 19.63 ± 11.82 stems ha-1. However there was no significant difference in densities between the villages in the study area (F 3, 195 =1.063, p= 0.366). There was a significant difference between marula tree diameters between arable and non arable land (t 92, 107 = 1.69, p = 0.0401). The arable land had generally bigger tree diameters (31.2 ± 25.3 cm) than non arable land (26.5 ± 20.8 cm), suggesting a form of domestication through allowing marula to grow around homesteads and crop fields. The investigation of marula size class profiles shows a large proportion of smaller diameter trees and this indicates ongoing recruitment of trees into the population. A closer analysis of the smallest diameter class shows a higher proportion of saplings (> 6cm diameter) than of seedlings (< 4cm diameter). Fruit harvesting seems to have a low potential for any negative impact, compared to other uses of marula trees. However fruits have the highest economic return and therefore should be targeted for the commercialisation activities. The management of some destructive forms of marula tree use (such as harvesting for bark, firewood, and carving wood) however, do need to be monitored to limit negative impacts on the population. There is also a need to determine the annual quantity of harvestable marula fruits and also the sex ratio of marula trees (a dioecious species) on this particular site, as a prelude to developing sustainable harvesting quotas, so that harvesting rates do not exceed the capacity of populations to replace the individuals extracted. There are some non governmental organisations (NGOs) and local institutions that are working towards natural resources conservation in the area. Zvishavane water project (ZWP) and Phytotrade Africa are assisting the rural producers in marula commercialisation activities through providing information on processing, packaging and marketing. At a current value of US$1 kg-1of fruit, the 3200 ha study area is estimated to yield a total harvest of 1 120 000 kg of marula fruit per year, and this should translate to an approximate total value of $1 120 000 per year for the whole area. There is still a need to expand the supply of processed goods with added value to wider markets locally, nationally, and internationally. There is therefore an indication that marula products offer a promising economic alternative for the people in the rural areas of Zvishavane area and southern Africa as a whole. The cash injection earned from selling fresh marula products comes at a particularly crucial time of the year, when money is required for school fees, uniforms and books. However there is a need for long-term monitoring and evaluation of socio-economic and environmental impacts of marula commercialisation so as to achieve sustainable resource utilisation in the region.
STUDENT NUMBER: 0516082G Master of Science in Resource Conservation Biology Faculty of Science
Keywords: Marula enterprise; Livelihoods; Regeneration; Commercialisation; Kokwaro trees; Nut oils; Zvishavane; Zimbabwe; Participatory rural appraisal (PRA); Arable land; Phytotrade Africa